Teachers’ Perceptions of the Effectiveness of Makaton for the Development of Basic Functional English in a Kazakhstani Nursery Classroom - Sin, Anna (Nazarbayev University Graduate School of Education, 2020)
The present study examined teachers’ perspectives of a visual support based language teaching tool ‘Makaton’ for preschool students in early years (EY) classrooms. The students were learning English as a foreign language, and the research focused on the extent to which they believe this tool facilitates the development of basic functional English for EY learners. This qualitative study collected data from class observations and interviews with teachers in a private EY school in the urban region of Kazakhstan. The results show that all participant teachers believe that using visual support enhances English language learning and assists in building basic vocabulary and communication skills. Teachers also discussed some of the challenges of using this tool in an EY environment. The results are useful for schools and EY pedagogues who are interested in exploring alternative methods to support preschool English learners.
Keywords: Makaton; second language acquisition; early childhood; ESL